"Rights for Life" scenario to reach biodiversity targets and social equity for indigenous peoples and local communities. (April 2023) - Sarkki, Simo; Pihlajamäki, Mia; Rasmus, Sirpa; Eronen, Jussi T.
Abstract: Scenarios are a powerful way in which the scientific community can inform future policies for transformative change. Forthcoming scenario work holds promise for the Nature Futures Framework, which through the concept of relational values, seeks to recognize a multiplicity of value positions on human-environment relations, including those of Indigenous Peoples and Local Communities (IPLCs). The objective of this Perspective paper is to propose a novel scenario skeleton titled "Rights for Life", which holds promise to achieve ambitious biodiversity targets in a socially-equitable ways by focusing on the Nature's and IPLCs' rights. We demonstrate, through the case of Arctic reindeer ( Rangifer tarandus tarandus ) herding, that the "Rights for Life" scenario seems to deliver better social equity outcomes than the recently proposed "Half Earth" and "Sharing the Planet" scenarios that have been designed to achieve ambitious conservation and biodiversity targets. The "Rights for Life" scenario is particularly fit for sparsely-populated indigenous homelands and rural regions where local communities depend on culturally important nature-based livelihoods for their well-being. We recommend that future scenarios targeting human-environment relations should not only consider non-western and relational value perspectives, but also recognize the importance of Nature's and IPLCs' rights for ensuring transformative change for equity and the environment. Clear recognition of such rights can function as a basis for new regulations, market-based governance instruments, policies, and participatory governance instruments ensuring that violation of Nature's and IPLCs' rights by societal developments is recognized, avoided, minimized, or at least compensated for. Highlights: The recently proposed "Half Earth" scenario represent the resurrection of fortress conservation. Even the collaborative "Sharing the Planet" scenarios, may fail to secure social equity for IPLCs. We propose the "Rights for Life" scenario skeleton to enhance social equity of biodiversity conservation for IPLCs. We elaborate the Nature Futures Framework by governance aspects regarding Nature's and IPLCs' rights. Recognition of relational values in nature conservation needs to be accompanied by explicit concern for IPLC's rights.